Simultaneous Estimation of Finasteride andTamsulosin Hydrochloride in Combined DosageForms by RP-HPLC-PDA Method - M. Sindhura, K. Raghavi, R. Prashanthi, Buchi N. Nalluri (Journal of Applied Pharmaceutical Science)
The study describes development and subsequent validation of an RP-HPLC-PDA method for the simultaneous estimation of Tamsulosin (TAM) and Finasteride (FIN) in bulk and tablet dosage form. The chromatographic conditions comprised of a reversed-phase C18 column (150 x 4.6 mm, 5 μ) with a mobile phase consisting of a mixture of methanol and formic acid (0.02% v/v in water) at a flow rate of 1 mL/min and ran in gradient mode. Detection was carried out at 230 nm. The retention times were 2.7 min and 10.08 min respectively for TAM and FIN. A good linear relationship in the concentration range 0.4-20 μg/mL with a correlation coefficient of 0.9981 for TAM and in the range of 5-50 μg/mL a correlation coefficient of 0.9987 was observed. Limit of detection (LOD) was found to be 0.16 μg/mL for TAM and 0.6 μg/mL for FIN. The method was validated for accuracy, precision, robustness and assay. The percentrecovery values were in the ranges of 99.15-100.8 for TAM and 99.21-101.83 for FIN. The results of all the validation parameters were well within their acceptance values.
Keywords: The study describes development and subsequent validation of an RP-HPLC-PDAmethod for the simultaneous estimation of Tamsulosin (TAM) and Finasteride (FIN) in bulk andtablet dosage form. The chromatog